(untitled) (Global Journal of Human-Social Science, 2025)
This research examines the impact of television cartoons on the socialization of youngsters in metropolitan Bangladesh Grounded in Cultivation Theory Social Learning Theory and Reception Theory it investigates the impact of sustained exposure to foreign and Hindi-dubbed cartoons on language utilization behaviour cognition and health A mixed-methods approach was employed to collect data via questionnaires from 130 parents supplemented by qualitative case studies Research indicates elevated levels of daily cartoon consumption 76 15 predominantly through mobile devices resulting in bilingual language usage 56 15 character imitation 40 heightened aggressiveness 36 92 and health issues including fast food cravings and screen addiction Notwithstanding the acknowledgement of negative consequences just 29 of parents impose restrictions on viewing The research underscores an urgent necessity for age-appropriate programming organized media literacy initiatives and more parental engagement It enhances comprehension of how mediated messages influence early experiences and necessitates immediate policy and educational reforms in media-saturated environments